A hydrogeochemical evaluation of groundwater in fractured rock aquifers using trace elements and stable isotopes at Loxton in the Central Karoo - Marais, Leander Hugo (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2001.